Highly porous Ni–P electrode synthesized by an ultrafast electrodeposition process for efficient overall water electrolysis. Issue 24 (12th June 2020) - Song, DongHoon; Hong, Doosun; Kwon, YongKeun; Kim, HyoWon; Shin, Jaewook; Lee, Hyuck Mo; Cho, EunAe
Abstract : A brief summary of the HP Ni–P for efficient overall water electrolysis. Abstract : The development of high-efficiency catalysts for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is essential to lower the energy losses during water electrolysis. Herein, a highly porous Ni–P (HP Ni–P) electrode, prepared by an ultrafast electrodeposition within only ten seconds, is presented with superior electrocatalytic activity towards both HER and OER in alkaline media: overpotentials of 96 and 323 mV are required to reach a current density level of 100 mA cm −2 for HER and OER, respectively, with corresponding Tafel slopes of 32.9 and 44.0 mV dec −1 . Experimental analyses and theoretical calculations show that charge transfer occurs from Ni to P and the HER kinetics is accelerated by the increased hydrogen coverage, enhanced water dissociation ability, and optimized hydrogen adsorption energy on the HP Ni–P. Under OER conditions, surface P is oxidized into PO4 3−, promoting oxidation of Ni to OER-active NiOOH and exposing abundant OER-active sites on the HP Ni–P surface. An alkaline electrolysis cell was constructed with HP Ni–P as the cathode and anode (Ni–P‖Ni–P) and outperformed the Pt/C‖IrO2 cell at cell voltages exceeding 1.68 V. This work provides a practically applicable method to prepare HER and OER electrodes for use in industrial water electrolyzers, with insight into the activities of the catalysts.